PENGARUH ASAN-FREE TRADE AREA TERHADAP PERTUMBUHAN EKPOR CRUDE PALM OIL INDONESIA 2003-2012 - Febrianti, Ria; Rani, Faisyal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
International trade that used in traditional and limited, now has progressed veryrapidly. The flow of goods can not be blocked even by doing a free trade agreement.Trade liberalization is intended for all countries in the world, has long been discussed bythe experts of the economy and also the leaders of the countries in the world. Attempts tobring this AFTA born of thinking about how to improve relationships (and also cooperation),especially in the economic field, which is closely among ASEAN membercountries. Entry AFTA will certainly impact the economic actors in each member state.The purpose of this study was to determine the influence of ASEAN Free Trade Area(AFTA) on the growth of Indonesias CPO exports Period 2003-2012. The results showedthat regional cooperation in the form of regional organization is still an option This isdue to the inability of developing countries to deal with the complex development ofinternational relations and the notion that regionalism can increase the level of theeconomy. Indonesia as a country that is known as a producer of CPO feel the influenceof the enactment of AFTA significantly to the development of palm oil exports. Given theopportunity CPO industry is promising, it is expected the Indonesian government tofocus on comparative and competitive advantages possessed.Kata kunci: Asean Free Trade Area, Crude Palm Oil